PENDAMPINGAN GURU SDN 155 ATAKKA SOPPENG DALAM INTEGRASI STEAM DAN KETERAMPILAN PROSES SAINS MELALUI PROYEK PEMBUATAN PUPUK ORGANIK CAIR BERBASIS SDGS - Nurhayati B; Ismail Ismail; Yusminah Hala; Suhartini Azis; Abdul Hadis; Muhammad Isrul; Andi Rahmat Saleh; Syamsul Syamsul (Jurnal Abdi Negeriku, 2026)
This community service program aimed to improve teachers’ understanding and skills at SDN 155 Atakka Soppeng in integrating STEAM and Science Process Skills (SPS) through an SDGs-based Liquid Organic Fertilizer (LOF) project. The program employed an empowerment-based mentoring approach consisting of socialization, training, hands-on LOF production, pre-test and post-test evaluation, and sustainability reflection. The pre-test indicated that teachers’ initial understanding of STEAM, SPS, and LOF was varied and not yet applicable. After mentoring, the post-test showed improved understanding, positive responses to the activity, and teachers’ ability to connect LOF with science learning activities, such as observing, measuring, drawing conclusions, and communicating findings. The hands-on activity also produced LOF with observable changes in color, odor, and texture, indicating the fermentation process. These findings demonstrate that the LOF project can serve as a contextual learning medium that connects teacher capacity building, STEAM learning, SPS development, organic waste management, and sustainability education in elementary schools. Further mentoring on LOF application, growing media, hydroponics, and formulation development is recommended to support sustainable environmentally-based IPAS learning.